Celsius Network - De Giusti, Marisa Raquel (2007)
The cooperative and collaborative work between Universities and Libraries are key points for teachers, researchers and students to make progress in their studies and research. The Library Linkage Initiative has pursued this purpose since its creation, and it has been very useful for many Institutions, Universities and Libraries in America and Spain, specially for those with scant resources. In PrEBi UNLP it has been created the Celsius software, which has become the standard application for management of users requests in the Initiative. The result of many years of use, improvement and experience acquisition has result in Celsius Network which has made a breakthrough in the Celsius development history. This last version intends to connect all instances of Celsius in a network, meeting the needs of users and operators that belong to the participants Institutions members of ISTEC. In the following article we have included a brief description of what ISTEC, LL Initiative and Celsius are -in order to present global view where Celsius Software fits- and a detailed description of users needs, new features and advantages in Celsius Network as well.